Anti-inflammatory and anti-proliferative effects of CBS3830 in arterialized vein grafts in rats. (December 2014) - Zhao, Zhi-Wei; Abendroth, Dietmar-Karl; Zhou, Zheng-Chun; Liu, Yong-Zhi; Pan, Fa-Ming; Ge, Jian-Jun
Abstract Objective: To investigated whether CBS3830, a highly selectively inhibitor of p38MAPK, could ameliorate inflammation and intimal hyperplasia in arterialized vein grafts (AVGs). Methods: Sixty male Sprague-Dawley rats underwent a reversed right jugular vein to common carotid artery interposition graft and were randomly treatment with vehicle (control) or single-dose (3 mg/kg, preoperative) or double-dose (3 mg/kg, preoperative and 4 d postoperative) CBS3830. Twenty rats underwent sham operation. The levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) were determined by ELISA. Vein grafts were analyzed by intimal/medial morphometry, proliferating cell nuclear antigen (PCNA) expression, and p38MAPK phosphorylation. Results: TNF-α, IL-1β, and IL-6 gradually increased then slowly decreased in AVG rats. However, at 4 d and 7 d, TNF-α levels decreased by 37.5% and 29.5% (p = 0.003, 0.05, respectively) in the single-dose CBS3830 group, and by 37.6% and 32.5%, respectively (both p = 0.003) in the double-dose group compared with those of control. IL-1β levels significantly reduced at 4 d and 14 d in both dosage groups. IL-6 levels significantly reduced at 7 d in both groups. Intima and medial thickening were significantly reduced in both dosage treated groups at 7, 14, and 28 d (all p = 0.000) compared to the controls. Further study showed CBS3830 inhibited p38MAPK phosphorylation and decreased PCNA expression. Conclusions: CBS3830 significantly decreases inflammation and intimal hyperplasia in AVGs.